Effect of salinity irrigation and seaweed extracts on vegetative growth and productivity of Barley (Comprehensive Journal of Science, 2025)
A experiment was conducted at Abu Hadi area-Sirte city, during the winter season 2022-2023 to study the effect of salinity irrigation and seaweed extracts on vegetative growth and productivity of Barley  (Hordeum vulgare, L.) cv., REHAN. The experiments were carried out in a split plot design with three replicates. Five salinity irrigation levels (control, 1000, 2000, 3000 and 4000 mg/l) were arranged in main plots and the other four seaweed extract (control, 2, 4 and 6 l/ha) were arranged in sub- sub plots. Each replicate contained 9 treatments. Studied characters were vegetative growth i.e. (plant height, number of tillers/m2, dry matter (g/m2), Total chlorophyll (SPAD), leaf area, (cm2) and yield and yield components (spike length (cm), spike weight (g), no. of  grains/spike, 100- grain weight, grain yield (t/fed), biological yield (t/fed) and harvest index (%). Results showed  that increasing salinity irrigation levels up to 4000 mg/l significantly decreased all vegetative growth were studied (plant height, number of tillers/m2, dry matter, total chlorophyll, leaf area) as compared to control treatment which recorded the higher values of this traits. On the other hand, seaweed extracts up to 6 l/ha recorded the highest values of all vegetative growth were studied (plant height, number of tillers/m2, dry matter, total chlorophyll, leaf area), as compared to control treatment which recorded the lowest values of this traits. In addition,  increasing salinity irrigation levels up to 4000 mg/l significantly decreased yield and yield component i.e. spike length, spike weight number of grains/spike, 1000-grain weight, grain yield, biological yield and harvest index, as compared to control treatment which recorded the higher values of this traits, while seaweed extracts up to 6 l/ha recorded the highest values of spike length, spike weight number of grains/spike, 1000-grain weight, grain yield, biological yield and harvest index, as compared to control treatment which recorded the lowest values of this traits. The interaction between salinity irrigation and seaweed extracts was highly significant on all vegetative growth and yield and yield component were studied under this study.
Keywords: Barley (Hordeum vulgare L.), salinity irrigation levels, seaweed extracts, vegetative growth, yield and yield components.